Rapid, Reliable and Accurate Method for Detecting of Pyrethroid Metabolite Contaminant in Synthetic Milk Using Gas Chromatography-Mass Spectrometry - Sonti, Parisa; Tummarintra, Paiboon; Keawbundit, Paklop; Wongman, Alisa; Duongkaew, Marisa (Thai Journal of Toxicology, 2022)
A rapid, reliable and accurate method for detecting the metabolited pyrethroid (cis/trans permethrinic acid) contaminant in synthetic milk using gas chromatography-mass spectrometry method was carried out. Fifty microliters of spike standard in milk (control, standard and all sample study) into 1.5 mL centrifuge tube. Then, it all evaporated by miVac at temperature 40 °C to dryness. Forward, added 50 µL of toluene (0.10 µg/mL of IS) and 20 µL of derivatizing reagent (MTBSTFA) into the tube and sonicated 10 min. Finally, the sample was incubated at 80 °C for 10 min before being injected into GC-MS. The validation parameters tested included selectivity, linearity, Limit of Detection (LOD), Limit of Quantification (LOQ), precision, and accuracy. The results showed that this method was selective, with only pyrethroid metabolite peaks detected. The method was linear in the concentration ranges of 0.05-10.00 μg/mL, with the coefficient of determination (R2) ≥ 0.995. The sensitivity (studied with LOD and LOQ) was 0.01 μg/mL and 0.05 μg/mL respectively. The accuracy and precision were passed the acceptance criteria with % recovery and % RSD of 83.85-104.54% and 1.50-5.82% for cis/permethrinic acid respectively, and 87.28-105.19%, and 2.44- 8.35% for trans/permethrinic acid respectively. The development method can monitor milk donation routines before giving the infant.